2006
DOI: 10.1016/j.virol.2005.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Immunization of rhesus macaques with a polyvalent DNA prime/protein boost human immunodeficiency virus type 1 vaccine elicits protective antibody response against simian human immunodeficiency virus of R5 phenotype

Abstract: The immunogenicity of a poylvalent HIV-1 vaccine comprised of Env antigens from primary R5 isolates was evaluated in rhesus macaques. DNA vaccines encoding four Env antigens from multiple HIV-1 subtypes and HIV-1 Gag antigen from a single subtype elicited a persistent level of binding antibodies to gp120 from multiple HIV-1 isolates that were markedly enhanced following boosting with homologous gp120 proteins in QS-21 adjuvant irrespective of the route of DNA immunization. These sera neutralized homologous and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 53 publications
5
68
0
Order By: Relevance
“…Recently, we demonstrated that a DNA prime-protein boost immunization strategy was effective in eliciting humoral and CMI responses in both small animals and non-human primates, including sterilizing immunity in a non-pathogenic SHIV model [16][17][18]. Our preclinical study results also indicated that this combination vaccination approach, but not recombinant protein alone, was effective in eliciting NAbs against primary HIV isolates [19], a finding that has been confirmed subsequently by other independent studies [20][21][22][23][24][25][26].…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…Recently, we demonstrated that a DNA prime-protein boost immunization strategy was effective in eliciting humoral and CMI responses in both small animals and non-human primates, including sterilizing immunity in a non-pathogenic SHIV model [16][17][18]. Our preclinical study results also indicated that this combination vaccination approach, but not recombinant protein alone, was effective in eliciting NAbs against primary HIV isolates [19], a finding that has been confirmed subsequently by other independent studies [20][21][22][23][24][25][26].…”
Section: Introductionsupporting
confidence: 75%
“…Although significant progress has been made using DNA immunization to elicit HIV-1-specific CMI in small animals, non-human primates and humans over the past 15 years [12][13][14][15][16]18,[38][39][40][41], there has been no report of using Env DNA immunization to elicit broadly crossreactive antibodies in humans. Levels of anti-Env antibodies elicited in previous DNA vaccine clinical trials were either low or undetectable [42,43], nor was there a clear induction of NAbs against even sensitive viruses [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we reported that a novel multi-gene, polyvalent DNA prime-recombinant protein boost HIV vaccine formulation, DP6-001, elicited strong and balanced humoral and cell-mediated immunity in healthy, HIV-1-negative adult subjects [1]. Preclinical testing of DP6-001 demonstrated no significant adverse reactions in either rabbits or non-human primates despite the induction of robust immunity [2,3]. Previously tested HIV DNA vaccines have demonstrated excellent human safety profiles [4][5][6][7][8][9].…”
Section: Hiv; Vaccine; Adverse Event; Vasculitismentioning
confidence: 99%
“…In this approach, the immune system is primed by administering the antigen of interest by one method (e.g DNA vaccine) and then boosted by a different one that delivers the same antigen (e.g recombinant protein, recombinant virus). A vast number of experiments have been performed in mice and non-human primates [139] and these strategies are already into clinical trials [140]. Detailed reviews on heterologous prime-boost strategies have been published elsewhere [3,[141][142][143].…”
Section: Heterologous Prime-boostmentioning
confidence: 99%